Sulfur-annulated perylenediimide as an interfacial material enabling inverted perovskite solar cells with over 20% efficiency and high fill factors exceeding 83%. Issue 37 (4th September 2019) - Wu, Fei; Luo, Zhenghui; Zhu, Linna; Chen, Chao; Lu, Huiqiang; Chen, Zhanxiang; Tang, Jiang; Yang, Chuluo
Abstract : An inverted PSC with a PDI-T interlayer exhibits an excellent efficiency of 20.41%, with a high fill factor (FF) of 83.63%. Abstract : Interfacial engineering is crucial for promoting the photovoltaic performance of perovskite solar cells (PSCs), especially planar inverted PSCs. In this study, sulfur-annulated perylenediimide (PDI)-based derivatives (denoted as PDI-T and PDI-V) with twisted molecular structures were developed for use as interfacial materials between the perovskite absorber and the C60 electron transporting layer. Benefiting from the decent electron mobility and good electron extraction and transporting properties of the PDI derivative-based interfacial materials, the charge transport is improved and the charge recombination at the interface is mitigated in the inverted PSCs. As a result, an inverted PSC with the PDI-T interlayer material exhibits a maximum efficiency of 20.41% and an excellent fill factor (FF) of 83.63%, representing one of the best values achieved in inverted PSCs. The PDI-V-based device shows a comparable efficiency of 20.17% and an excellent FF of 82.98%. The efficiencies over 20% achieved in this study are among the highest values reported to date in methylamine-based inverted PSCs.